Trabalho e estudos em tempos de pandemia: olhares de jovens do ensino médio público paulista - Siqueira, Gabriel Di Pierro (2023)
The present research aimed to understand, based on an effort to approximate their realities, how the most recent social transformations - in particular the context of the covid-19 pandemic - impact the trajectories of young students of public high schools in the state of São Paulo. This is a quantitative and qualitative investigation that took place throughout 2021 and 2022 with ten different public schools of regular high school and technical education located in the municipalities of São Paulo, Sorocaba and Santos, with young students between 15 and 18 years old, participants of a Scientific Pre-Initiation Program aimed at high school. It sought to learn about youth experiences that unfold in three large dimensions: studies, work and future prospects. Supported by studies of Sociology of Youth, the investigation considered the profound historical transformations that had repercussions on less linear and more heterogeneous study and work trajectories. The construction of research instruments and field analyzes were inspired by the theoretical production of sociologist Danilo Martuccelli around a sociology of individuation, which proposes the study of social phenomena from the scale of individuals, seeking to understand macrosocial and historical movements from of an approximation of individual trajectories and narratives. Students' reports indicated very significant impacts of the health crisis on their schooling processes, producing the perception of a loss of school knowledge and negatively affecting projects for access to higher education. Young people also reported an overload of activities, which most strongly affected students who worked and young women who performed unpaid domestic work. Faced with the context of uncertainties, increased inequalities and lack of support, a significant number of young people mobilized efforts to invest in training and work activities, seeking to guarantee more favorable future prospects. The challenges posed increased tensions between what young people wanted for themselves and the concrete conditions to carry out their projects, producing consequences for their mental health.